2015
DOI: 10.1073/pnas.1501529112
|View full text |Cite
|
Sign up to set email alerts
|

New chronology for Ksâr ‘Akil (Lebanon) supports Levantine route of modern human dispersal into Europe

Abstract: Modern human dispersal into Europe is thought to have occurred with the start of the Upper Paleolithic around 50,000–40,000 y ago. The Levantine corridor hypothesis suggests that modern humans from Africa spread into Europe via the Levant. Ksâr ‘Akil (Lebanon), with its deeply stratified Initial (IUP) and Early (EUP) Upper Paleolithic sequence containing modern human remains, has played an important part in the debate. The latest chronology for the site, based on AMS radiocarbon dates of shell ornaments, sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
67
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(73 citation statements)
references
References 54 publications
5
67
0
1
Order By: Relevance
“…45 ka, Russia; Fu et al, 2014), Ksar Akil (ca. 45e40 ka, Lebanon; Bosch et al, 2015;Douka et al, 2013), Peş tera cu Oase (ca. 42e38 ka, Romania; Trinkaus et al, 2003), Fumane and Bombrini (ca.…”
Section: Table 14mentioning
confidence: 99%
See 1 more Smart Citation
“…45 ka, Russia; Fu et al, 2014), Ksar Akil (ca. 45e40 ka, Lebanon; Bosch et al, 2015;Douka et al, 2013), Peş tera cu Oase (ca. 42e38 ka, Romania; Trinkaus et al, 2003), Fumane and Bombrini (ca.…”
Section: Table 14mentioning
confidence: 99%
“…The spread of Proto-Aurignacian characteristics, such as bladelets and bone tools, can seemingly be traced back to the Kozarnikian in Bulgaria and the Levantine Ahmarian (Bar-Yosef, 2000;Mellars, 2006;Hoffecker, 2009;Hublin, 2015;Bosch et al, 2015; but also see; Kadowaki et al, 2015). Because of similarities with the IUP Levantine Emirian (Bar-Yosef, 2000), the Bohunician (Moravia) has also been proposed as a candidate for an intrusive, probably modern human, origin (Svoboda and Bar-Yosef, 2003;Bar-Yosef, 2007;Tostevin, 2003;Skrdla, 2003;Hoffecker, 2009;Nigst, 2012;Kuhn and Zwyns, 2014;Hublin, 2015).…”
Section: Table 14mentioning
confidence: 99%
“…The Mediterranean basin has long been considered to be an important area for understanding the dispersal of Homo sapiens from Africa to Eurasia. This is particularly the case during the ~40,000–50,000‐years‐ago window that appears to have led to the establishment of populations in Eurasia equipped with various Upper Paleolithic technologies . Morphological and genetic data from sparse hominin fossils indicate the initial appearance of H. sapiens in western Eurasia north of the Mediterranean Sea during this time, although the reasons for the geographic expansion of our species as well as potential archeological evidence for it remain highly debated .…”
Section: Introductionmentioning
confidence: 96%
“…The oldest, largely accepted dates of humans outside of Arabia all fall around 50-40 kya regardless of whether in Asia, Australia, or Europe (10,11,(40)(41)(42)(43). However, as already indicated, not only have several studies suggested older dates, but the chances of finding the oldest evidence are so slim that oldest dates must inevitably get older.…”
mentioning
confidence: 92%